Other-initiations of repair in Norwegian Sign Language - Skedsmo, Kristian (Social Interaction. Video-Based Studies of Human Sociality, 2020)
During the last five decades, a substantial amount of research has been conducted into conversational repair (Schegloff, Jefferson, & Sacks, 1977), and especially other-initiation of repair (OIR). A vast part of the research has been on spoken English, without considering or having access to embodied practices. Through a series of examples, this explorative paper provides a brief overview of formats and subtypes of other-initiation of self-repair employed in Norwegian Sign Language (NTS). Special attention is given to the implicit open-class repair-initiation “freeze-look”, as identified by Manrique (2016), Manrique and Enfield (2015), and Manrique, Enfield, Levinson, Crasborn, and Floyd (2017) in Argentine Sign Language, and to the subtype of restricted repair-initiations categorized as candidate offers. The data has been extracted from a corpus of informal multi-person conversations among deaf adult co-workers, recorded at their workplaces. The results show a high degree of overlap with formats found in spoken languages, but also highlight features that seem to be unique to signed languages and the visual mode of communication. The examples presented take the form of summaries, transcriptions, uncensored video clips, and series of stills.